Intimate relationships : issues, theories, and research - Erber, Ralph; Erber, Maureen Wang (New York, NY : Routledge, 2024)
"The fourth edition of this bestselling textbook offers a comprehensive examination of intimate relationships. It covers classic and contemporary scholarship of the psychology of relationships, presenting the material in an engaging and rigorous manner. The book covers a range of themes to explore the multifaceted dimensions of relationships, from the evolution of attraction and love to the intricacies of attachment and complexities of jealousy. Written in a warm and personal voice, each chapter features real-life stories to stir readers' engagement, while critical thinking prompts encourages reflection on both the presented issues and theories. Adopting an interdisciplinary perspective firmly anchored in research, this new edition stays abreast of the evolving landscape of relationship science. It has been carefully updated to present the latest findings and includes new material on intriguing subjects such as sexual pathways, online dating, the far-reaching impact of COVID-19, open science, and the diverse fabric of 21st century relationships- including interracial and LGBTQ+ dynamics, cohabitation, and singlehood. Written for students and any reader keen on understanding the intricacies of romantic relationships, Intimate Relationships is ideal reading for undergraduate students of psychology, sociology, and related disciplines, or as an enriching supplement for graduate studies"--
Keywords: Man-woman relationships; Interpersonal relations; PSYCHOLOGY / General; PSYCHOLOGY / Emotions; PSYCHOLOGY / Interpersonal Relations